Foraging ecology of the amphibious mudskipper Periophthalmus chrysospilos (Gobiiformes: Gobiidae) - Quang Minh Dinh; Ton Huu Duc Nguyen; Tran Thi Huyen Lam; Tien Thi Kieu Nguyen; Giang Van Tran; Zeehan Jaafar (PeerJ, 2021)
The food composition and feeding ecology of fishes living in the intertidal zone play an essential role in understanding the energetic connectivity between terrestrial and aquatic systems. Periophthalmus chrysospilos is an amphibious fish species occurring in the intertidal zone, but data on its diet and foraging ecology is still poorly known. This study on Ps. chrysospilos was carried out from April 2020 to March 2021 at four sites within the Mekong Delta estuary to define the influence of spatio-temporal factors on the diet of this species. The diet composition and relative gut lengths (RGLs) of Ps. chrysospilos were analysed in relation to four parameters—sex, size, site, and season. A total of 1,031 individuals were collected, and their digestive tract lengths were used to calculate the RGL. The digestive tracts of only 546 individuals were with food items (approximately 1:1 of empty vs full digestive tract) and were subsequently used for further analyses. The ranges in total length and weight in both adult and juvenile individuals were 3.4–10.6 cm and 0.38–14.13 g, respectively. The RGL values varied with season, fish size and site, but was always lower than 1, indicating a predominantly carnivorous diet. The variability of food items found within the digestive tracts demonstrated its adaptability in pursuing prey items within the limits of the littoral zone, and its importance as a conduit of terrestrial-marine connectivity. This species is characterised as an opportunistic mesopredator feeding primarily on Acetes spp., Uca spp., Dolichoderus sp., and rarely on Polychaeta and Actinopterygii. Other items found within the digestive tract are Mollusca, and detritus. The diet composition of Ps. chrysospilos did not vary with season and size, but changed with sex and site parameters. Uca spp. contributed to the sexual variation in dietary component, whereas Mollusca, Uca spp., Dolichoderus sp. and detritus, were drivers for spatial variation in the dietary component. The research provides fundamental information on diet composition and feeding strategy, as well as contributes towards knowledge on foraging ecology and resource use by intertidal animal communities.